Dynamic changes in metabolic and lipidomic profiles of tea plants during drought stress and re-watering - Shen, Jiazhi; Wang, Shuangshuang; Sun, Litao; Wang, Yu; Fan, Kai; Li, Chen; Wang, Hui; Bi, Caihong; Zhang, Fen; Ding, Zhaotang (Frontiers in Plant Science, 2022)
The evergreen plant tea (Camellia sinensis L.) needs a humid environment. Water deficit would diminish tea yield and quality. We analyzed the dynamic changes in metabolite and lipid profiling of tea leaves under various drought conditions and re-watering to determine the metabolic changes in tea leaves responding to drought challenges. In all, 119 metabolites showed substantial alterations in drought-stressed tea plants, including sugars and sugar alcohols, amino acids, and tricarboxylic acid cycle intermediates. Phosphatidylglycerol (PG), phosphatidic acid (PA), sulfoquinovosyl-diacylglycerol (SQDG), phosphatidylcholine (PC), lyso-phosphatidylcholine (LysoPC), and phosphatidylinositol (PI) were among 29 lipid compounds found. Sugar and sugar alcohol levels, as well as those of its precursors, may change as a response to drought stress. Compared with these metabolites, the membrane lipids showed more dynamic changes in tea under drought stresses. Furthermore, metabolic recovery was only partial, with majority of the examined metabolites exhibiting significantly different levels between samples from re-watered and well-watered tea plants. The findings also showed that comprehensive metabolomic and lipidomic approaches were efficient in elucidating the impacts of drought stress on tea plant metabolism. Our findings are valuable for understanding the mechanisms behind drought tolerance in tea plants in the metabolism perspective and utilizing the compounds to improve drought tolerance of tea plants.